Karen's kittycat club - Martin, Ann M.; Farina, Katy (New York : Scholastic / Graphix, 2021)
"Karen's best friend Hannie just got a new kitten. Now all her friends have cats, and Karen has a great idea. She can start a Kittycat Club! What will the club do? Karen can't baby-sit like her big sister Kristy... but she can cat-sit! Will anyone want Karen as a cat-sitter? Karen hopes so!"--
Ages 7-10
Grades 2-3